XV International Conference Noise Control 2010 - ZAWIESKA, Wiktor M. (Archives of Acoustics, 2010)
Noise Control is the most important international acoustics conference regularly organized in Poland. The XV International Conference Noise Control 2010 is taking place between June 6 and 9, 2010, in Książ in Wałbrzych. It is organized by the Central Institute for Labour Protection - National Research Institute, the Committee on Acoustics of the Polish Academy of Sciences, the Polish Acoustical Society, with the cooperation of the Department of Mechanics and Vibroacoustics of the AGH University of Science and Technology, the Department of Acoustics of the Building Research Institute and the Chair of Acoustics of the Wrocław University of Technology.